SISTEM INFORMASI PENGELOLAAN JAMINAN KREDIT PADA BPR MCM MENGGUNAKAN ARSITEKTUR N-TIER - Rubi Tridarta Sandiraga; Sujito; Weda Adistianaya Dewa (Sekolah Tinggi Manajemen Informatika & Komputer PPKIA Pradya Paramita Malang, 2025)
BPR Mitra Catur Mandiri (BPR MCM) is one of the Rural Bank serves the provision of credit, savings and deposits to customers both for personal use and development of micro enterprises. PT. BPR Mitra Catur Mandiri also provide facilities to the debtor to replace the collateral. Recording replace the current collateral using book of registers and application that named SOLegal where the application is not able to record the history of data collateral. In addition, the Credit Division and Legal Division annoyed the demand list of installments and collateral the debtor in exchange for collateral process. The method applied in this study is the method of application architecture and system development methods. Method of application architecture used is N-Tier Data Application web based. While the system development method used is the System Development Life Cycle (SDLC) to the stages of software requirement analysis, design, program code generation, testing, support or maintenance. The result showed that the use of N-Tier architecture, management information systems collateral can be accessed from the central office and branch office and be able to record the history of the initial collateral when credit disbursement and after replacing the collateral.